(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
The article describes important tasks in the implementation of the concept of development of mathematics education, comprehensive improvement of mathematics education and bringing it to a new level of quality. It was emphasized that mathematics is the basis of knowledge of the universe, its importance in revealing the unique laws of surrounding events and phenomena, production and development of science cannot be imagined without mathematical knowledge.